Improving Students’ Writing Skill in Narrative Text by Using Storybird: at Grade X Teknik Komputer Jaringan 1 of SMK Yayasan Pendidikan Persada Indah (YPPI) Tualang - Andriani Refika; Wahyuni Devi (Universitas Lancang Kuning, 2018)
This research was aimed at improving writing skill in narrative texts by using storybird for Grade X Teknik Komputer Jaringan 1 students of SMK Yayasan Pendidikan Persada Indah (YPPI) Tualang, Kabupaten Siak in the academic year of 2017/2018. This particular research was categorized as action research. The actions were implemented in two cycles based on the class schedule. The researcher worked collaboratively with the English teacher, as the collaborator and the students. The subjects of the research were 20 students of class X Teknik Komputer Jaringan 1 of SMK Yayasan Pendidikan Persada Indah (YPPI) Tualang, Kabupaten Siak in the academic year of 2017/2018. The data of the study were taken by using test, observation checklist, field note, and interview. The research findings showed that the use of storybird in teaching writing narrative texts was able to improve the students’ writing skills. It included their abilities in generating ideas, vocabularies, language use and mechanics. Based on the quantitative data, the students’ based score was 71.70 and increased into 72.30 in the test of Cycle I and became 85.30 in the test of Cycle II. Then, the gain score was 13 points. There were several factors that influence the improvement, such as the students’ interest with social media like storybird. They enjoyed writing narrative text in storybird and being more creative. Besides, teaching writing narrative texts using storybird could attract students’ attention and motivation. The students became more enthusiastic in writing after using storybird in the class It indicated that the students made a considerable improvement in writing narrative texts.